Efeitos da Inicialização na Formação de Emaranhamento Quântico em Qubits de Carga - Fernandes, Ellen Martins (2024)
The effects of electronic initialization of quantum states on the entanglement in electronic systems remain an open question. Our research focuses on a system model comprising of quantum dot molecules attached to electronic reservoirs. Two electronic qubits interact with each other via Coulomb repulsion. The interplay between Coulomb and hopping process results on the formation of entangled states. Here we analyse how a Gaussian gate voltage pulse, that injects electrons into the qubits in a time controlled way, can interfere on the entanglement degree. To this aim we calculate different quantities such as fidelity, Von Neumann entropy and negativity . Ours results show that the proper adjustment of the initialization pulse width is crucial to the formation of highly entangled states, thus shining light on possible future experimental implementation of electronic qubits.